PENGEMBANGAN VIDEO PEMBELAJARAN DENGAN SOFTWARE CAPCUT PADA MATERI GELOMBANG BUNYI - Khasanah, Intan Nahdiyatul; Perdana, Riki (Jurnal Inovasi Penelitian dan Pembelajaran Fisika, 2023)
Learning media is one factor in increasing students' learning motivation. So, it is necessary to develop learning media that attract students' learning interest and activeness in class. This development research aims to develop learning media that is oriented towards the use of technological developments. This research uses a 4D research model, which has 4 stages starting with definition until the final stage is dissemination. The research instrument used was a questionnaire instrument for the validity of video learning media. The results of this research are learning media in the form of videos created using CapCut software which is currently popular among young people. The learning video that was developed showed an average feasibility result of 88% with the category very suitable for use in learning sound waves.